LAPORAN ARUS KAS, PRODUKTIVITAS KARYAWAN PADA KINERJA PERUSAHAAN : BUKTI DARI PERUSAHAAN FOOD AND BEVERAGE - Mishelei Loen (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to examine the effect of Cash Flow Statements and Employee Productivity on the Performance of Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2019 – 2022. The data used in this research is quantitative data. The sampling technique used purposive sampling obtained a total number of samples. 76 data. The results of the study show that the Cash Flow Report as measured by Operating Cash Flow (AKO) has a positive and significant effect on company performance; Employee productivity as measured by Revenue Per Employee (RPE) has a positive and significant effect on company performance; Statement of Cash Flow as measured by Operating Cash Flow (AKO) and Employee Productivity as measured by Revenue Per Employee (RPE) has a positive and significant effect on company performance